Power quality and reactive power compensation study - Nurul Fatihah, Mohamad (2010)
Power quality is an issue that is becoming increasingly important to electricity consumers at all levels of usage. There are many major cause effected on this quality of power. In this research, power quality and reactive power compensation in electric radial distribution networks will be analyzed using industrial data network and modeled by using DigSILENT PowerFactory software as for simulation. This thesis presents an approximate technique of capacitor placement for loss minimization and power quality as well. In order to analyze for this system it suppose to be concern on the sizing and placement of the capacitors. So then, the power loss is minimized and annual savings are maximized